PENERAPAN SISTEM MEKANISASI DALAM KEGIATAN PENEBANGAN JATI UNTUK MENGURANGI KETERGANTUNGAN TERBATASNYA PENYEDIAAN TENAGA BLANDONG DI JAWA - Maman Mansyur Idris; Soenarno Soenarno (Jurnal Penelitian Hasil Hutan, 1990)
Sastrodimedjo, (1975) pointed out that the present trend of wood processing  industry development and formal education of younger  generation  caused some problems,  especially in the sustainabiliy  of forest  worker supply  in Java.Based on this  consideration  an  alternatif   for  most  widely  applied  felling  system,   i.e.  manual  felling  system, needs to  be sought. With  regard to this problem a study  was conducted at three Sub Forest District (RPH), namely Temenggeng, Pasar Sore and Sumberogo in Central Java to compare  3 (three)   felling  systems  in teak forest.The result  of  the  study  revealed  that  the  teak  felling  productivity  averages on 2 years gilrded  teak with  mechanical, manual  and  combination systems applied to flat  terrain  were 2.5359 m3/hour,  0.7128  m3/hour and  0.8186 m3/hour, respectively. But   those on hilly terrain were 1.5540 m3/hour, 0.7374 m3/hour and 0.796 m3/hour,   respectively.   The average cost  of  full  mechanical  felling  system applied to flat  terrain  was Rp 1,586.23/m3,  while  that  of on  hilly  terrain was Rp 2,l  65.93/m3